Unilateral Visual Loss after a Nasal Airway Surgery. Issue 6 (January 2013) - Awad, J.; Awad, A.; Wong, Y.; Thomas, S.
Septoplasty and turbinoplasty are common ear, nose, throat (ENT) operations which generally have low complication rates. A 45-year-old man had a septoplasty operation and a right turbinoplasty operation under a combined general and local anesthetic. He woke from the procedure with a reduced visual acuity in the right eye and substantial inferior visual field loss. A review of the current literature focuses on the vasospasm effects of local anesthetic, in combination with epinephrine on the intricately linked nasal and orbital vascular supply.